An Adaptive Web-based Framework for Mobile Telemonitoring System - Setyono, Andik; Haryanto, Hanny; Astuti, Erna Zuni (International Journal of Interactive Mobile Technologies (iJIM), 2017)
Mobile long distance monitoring system using web-based will be deliberated as one of the primary industry in the near future. This paper focuses on the development of the healthcare service for telemonitoring system using an adaptive web-based framework with several parameters at the same time. The proposed system is used to make easy the patient and physician for accessing healthcare system. It tries to combine many functions in healthcare services for long distance monitoring system. Physiological parameters are used such as blood pressure, blood sugar, respiration, heartbeat, pulse, temperature will be received by the system then it is sent to the clinic server immediately. All of these parameters can be inputted by patients themselves while the patients are far from the clinical environment and forward to the physician for further diagnosis and medical treatment. The advantages of the proposed system are the patient will be easy to access the system through internet and easy to connect the physician from a remote area. Smartphone with multimedia features and internet connection in mobile environment can be used to perform mobile computing anywhere and anytime. It keeps real-time recording and monitoring of physiology parameters of the patients at lowest cost and at home. The physiology parameters of patient are increased to be multimedia data. By using the good quality of the multimedia data, the physician will be more precise to perform diagnosis and medical treatment to the patient. The proposed framework can be used to develop a practical web-based mobile telemonitoring system in mobile environment.